Israel in Egypt: the land of Egypt as concept and reality for Jews in antiquity and the early medieval period - Salvesen, Alison ca. 20./21. Jh.; Pearce, Sarah Judith Katharine; Frenḳel, Miryam (Ancient Judaism and early Christianity, 2020)
"In Israel in Egypt scholars in different fields explore what can be known of the experiences of the many and varied Jewish communities in Egypt, from biblical sources to the medieval world. For generations of Jews from antiquity to the medieval period, the land of Egypt represented both a place of danger to their communal religious identity and also a haven with opportunities for prosperity and growth. A volume of collected essays from scholars in fields ranging from biblical studies and classics to papyrology and archaeology, Israel in Egypt explores what can be known of the experiences of the many and varied Jewish communities in Egypt, from biblical sources to the medieval world"--